Tingkat Kesesuaian Lahan Tembakau Deli (Nicotiana tobacco L.) pada Beberapa Subgroup Tanah di Sumatera Utara - Khusrizal Khusrizal (Jurnal Agrista, 2006)
Land Suitability Level for Deli Tobacco (Nicotiana tobacco L.) of Some Soil Subgroup in North SumateraABSTRACT. A field experiment was aim to study land suitability classes based on the limiting factor of growth for deli tobacco of soil subgroups (Aquic Eutrudepts, Aeric Epiaquepts, Fluventic Eutrudepts) was conduct at deli tobacco plantations PT. Perkebunan Nusantara II. The experiment carried out by using soil data (database and soil analysis), wet production leaf and rainfall for tenth year period (1992 – 2001). The result showed that the plantations of deli tobacco classified in to land suitability classes; S3tn (Aquic Eutrudepts), S3dn (Aquic Eutrudepts; Aeric Epiaquepts), S3n (Aquic Eutrudepts; Fluventic Eutrudepts) and S3wn (Aquic Eutrudepts) with the limiting factors of growth such as low water content, poorly drainaged, fine texture, low organic-C, low total-N, low soil pH, low cation exchange capacity (CEC), highly available – P. The land suitability class of S3tn has the higher wet leaf production than S3dn, S3n, and S3wn. The lowest is land suitability class of S3wn. The wet leaf production, organic – C and soil pH have significant positive correlation (r = 0.57**), (r = 0.43*) and (r = 0.44*). The soil subgroup of Aeric Epiaquepts is able to produce higher wet leaf production than soil of Aquic Eutrudepts and Fluventic Eutrudepts.